Sodobno vodenje trajne astme - Košnik, Mitja (Obzornik zdravstvene nege, 2006)
Asthma afflicts at least 5% of the population. The patients have difficulties in breathing because air ways are narrowed due to the inflammation process. Measures which abate asthma inflammation help to control the disease. The inflammation is coped with by elimination of allergens and irritants and, above all, by use of antinflammatory drugs. Research performed on the control of asthma all over the world reveal that in everyday life, not many patients achieve such a degree of control over the disease as it has been proven possible in clinical research. The weak point of clinical directions used for asthma control at the moment lies in the fact that they are mostly drug prescription oriented. The fact remains that the course of the disease can be most efficiently influenced upon by health education and by intensifying the patient''s own engagement in the treatment process.
Keywords: Asthma; Astma; Classification; Diagnosis; Drug Therapy; therapy; zdravljenje; zdravstvena vzgoja